2009
DOI: 10.1073/pnas.0901454106
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating germ-line and somatic mutations in polypeptide N -acetylgalactosaminyltransferase 12 in human colon cancers

Abstract: Aberrant glycosylation is a pathological alteration that is widespread in colon cancer, and usually accompanies the onset and progression of the disease. To date, the molecular mechanisms underlying aberrant glycosylation remain largely unknown. In this study, we identify somatic and germ-line mutations in the gene encoding for polypeptide N-acetylgalactosaminyltransferase 12 (GALNT12) in individuals with colon cancer. Biochemical analyses demonstrate that each of the 8 GALNT12 mutations identified inactivates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 15 publications
5
123
0
Order By: Relevance
“…Additionally, these studies also identified O-glycans on mammalian Tango1/Mia3 (26,27), suggesting that O-glycans may perform similar protective functions to control secretion in mammalian systems. Indeed, alterations in both Tango1/Mia3 and O-glycosylation have been associated with diseases of the mammalian gastrointestinal tract (5,6,28,29), which are typically characterized by loss of secretion, loss of mucous membrane formation, and increased diffusion barrier permeability. Interestingly, PGANT4 is most similar to the mammalian ppGalNAc-T10 (8), which is abundantly expressed in the digestive system (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these studies also identified O-glycans on mammalian Tango1/Mia3 (26,27), suggesting that O-glycans may perform similar protective functions to control secretion in mammalian systems. Indeed, alterations in both Tango1/Mia3 and O-glycosylation have been associated with diseases of the mammalian gastrointestinal tract (5,6,28,29), which are typically characterized by loss of secretion, loss of mucous membrane formation, and increased diffusion barrier permeability. Interestingly, PGANT4 is most similar to the mammalian ppGalNAc-T10 (8), which is abundantly expressed in the digestive system (30).…”
Section: Resultsmentioning
confidence: 99%
“…Polarized secretion is also required in many differentiated tissues, such as the digestive tract, where secreted components along the apical surface form the mucous membrane that confers protection from mechanical and microbial insults (1) and provides immunoregulatory signals (2). Indeed, disruptions in the secreted mucous membrane are associated with diseases of the digestive tract, such as colitis and colon cancer (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The repertoire of enzyme isoforms expressed in cancer cells is markedly altered from the normal counterparts (29)(30)(31)(32)(33)(34); however, the consequences of these changes for the O-glycoproteome and carcinogenesis remain unknown. The locus 9q22 including the GALNT12 gene is a susceptibility locus for colorectal cancer (35) and heterozygous germ line as well as somatic inactivating mutations have been identified in cancer patients (36). GALNT12 is thus a prime candidate for the proposed strategy.…”
Section: Discussionmentioning
confidence: 99%
“…4) have been reported in several individuals with colon cancer [56]. Some of the mutations were detected in the germline of the patients, whereas other mutations were somatic and localized to the tumors themselves.…”
Section: Polypeptide Galnac-transferase-12mentioning
confidence: 99%
“…Some of the mutations were detected in the germline of the patients, whereas other mutations were somatic and localized to the tumors themselves. Although it is unclear whether the decreased GALNT12 activity affects O-glycosylation in colon tissue, increased antibody reactivity towards unglycosylated MUC1 mucin protein was found in several colon tumors [56].…”
Section: Polypeptide Galnac-transferase-12mentioning
confidence: 99%